The occurrence of a testicular coccidian Eimeria sardinae (Thélohan, 1820) (Reichenow, 1921) in southern Africa sardine Sardinops sagax (Jenyns, 1842) - Ssempa, Nurudean Norman (Department of Biological Sciences, 2014)
Includes bibliographical references.